Kroppens förvandlingar - Jonas Frykman (Kulturella Perspektiv, 1994)
Alternative medical practices have expanded rapidly since the late 1960s. In the present article, this is viewed as one of the many cultural forms through which life-policy questions are brought onto the social and political agenda. It could be regarded as a metasocial commentart, on of the many arenas wherein people attempt to delineate another type of relationship between themselves and society. The emphasis is placed more upon "being" than on "becoming", a tendency which fits in well with the overall debate concerning identity-formation during the late modern era. The article further argues that during the first half of the century, ordinary or "school" medicine bore the Utopian message of a modern welfare society, a society in which there ought not exist any differences based on family, social background or financial status. The much-discussed "medicalization" had in fact much to say about matters such as equality and modernity.